Efficacy of Cefquinome against Escherichia coli Environmental Mastitis Assessed by Pharmacokinetic and Pharmacodynamic Integration in Lactating Mouse Model - Yu, Yang; Fang, Jin-Tao; Sun, Jian; Zheng, Mei; Zhang, Qing; He, Jie-Shun; Liao, Xiao-Ping; Liu, Ya-Hong (Frontiers in Microbiology, 2017)
This work investigates the pharmacodynamic effectiveness of cefquinome against environmental Escherichia coli mastitis infection, following an intramammary administration. We established the pharmacokinetic and pharmacodynamic (PK/PD) model in lactating mice. The PK/PD parameters were identified to achieve an antibacterial efficacy as indicated by PD activity, cytokine expression and PK/PD simulation. From our findings, given an 200 μg/gland dose once daily can achieve a considerable therapeutic effectiveness in experimental circumstance.